Imagery and Portrait in Majeed Amjad's Poetry - Ejaz Ahmad (بازیافت, 2021)
The purpose of imagery in poetry is to send the message of poet in a strong, vivid and in a very visual voice. The poet uses words to create images in our mind that helps to interpret poem in a way he sees it. He uses similes, metaphors and personifications to create mental picture through words that gives a strong message to understand the poet's message. To indicate the points which seem the most vivid and important to reader, the writer allows the reader to flesh out their sketch into a portrait. In other words, you can think of imagery as painting with words in order to fuel the reader's imagination. Majeed Amjad mellowed as a poet in the late 34s. He is a painter, like Ustad Allah Bakhsh, involved in aesthetic and classical landscape in his poetry. This involvement is not static or superficial. This article reflects a brief introduction of imagery and Majeed Amjad's art of using images in his poetry5